South Cushitic Classification in Lexicostatistic Perspective - Blažek, Václav (Folia Orientalia, 2019)
A purpose of the present study is an evaluation of various models of classification of the South branch of the Cushitic languages. The South Cushitic languages are studied in their narrow sense here, i.e. without Dahalo and Ma’a, although their probable cognates are registered.